Developing a Community Forestry Program - Nighswonger, James J. (My University, 1998)
A community forestry program is sponsored by city government to provide for planting, care, and removal of trees on public property — trees in parks, along streets, right-of-ways, and similar areas.
L833_1998-04
Keywords: L833; Forestry; L